APPRECIATIVE INQUIRY AS A WAY OF CORPORATE SOCIAL RESPONSIBILITY MANAGEMENT - tymoshenko, dmytro (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The purpose of the article is to substantiate the need for the practice of appreciative inquiry (AI) both in general and when conducting activities on corporate social responsibility. The goal is supported by the goals of studying the potential of appreciative inquiry with an emphasis on the compatibility of the practice of the appreciative inquiry method with the practices of corporate social responsibility. The history of the development of appreciative inquiry is studied. It is indicated that the scientific activity of Ukrainian authors on this topic in the field of economic sciences has not been found. The relevance of the research is due to the need for a mechanism for the systematic identification of what supports the modern socio-economic system in the context of the dynamics of its economic, socio-ecological and other components. For this, the method of appreciative inquiry was considered from the standpoint of "philosophy of management", which consists in asking those questions that increase the system’s ability to cooperate, make it possible to realize the strengths of people, processes and technologies and their positive potential, and also help to unite around big ideas and high meanings. Attention is paid to the compatibility of the essence of appreciative inquiry with the essence of corporate social responsibility, with justification of the feasibility of using appreciative inquiry to strengthen the practices of corporate social responsibility. The essence, structure, principles and theories underlying appreciative inquiry are considered. The cycle of implementation of appreciative inquiry is illustrated, as well as examples of its application by well-known enterprises and organizations. On this basis, an algorithm for the use appreciative inquiry in corporate social responsibility is presented. As a method of strengthening the corporate social responsibility of the Ukrainian socio-economic systems, it is proposed to use the principles of the philosophy (values) of the Maori people — kaupapa Maori to improve well-being, politics, ethics, etc. in the context of sustainable development.